Method for leak testing of sample containers

By laying anhydrous copper sulfate powder into the inner wall of the sample container and testing it in a water or steam environment, the problem of complex and high cost of sample container leakage testing in the prior art is solved, and rapid and low-cost leakage detection is achieved.

CN118730419BActive Publication Date: 2025-03-14SCIVITA MEDICAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411221032.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-03-14
Estimated Expiration
2044-09-02

AI Technical Summary

Technical Problem

The methods used in the prior art for sample container leakage testing are complex in operation, have many equipment requirements, have long test cycles and high costs, and many third-party laboratories do not have such testing qualifications.

Method used

Whether leakage occurs based on the color change of the discolored substance is determined by laying anhydrous copper sulfate powder into the inner wall of the sample container as a discolored substance, and immersing the container in water or placing it in a steam environment.

Benefits of technology

It realizes a leak testing method that is simple, fast and low-cost, without additional testing equipment, fast test speed, high sensitivity, and can complete self-tests in a short time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118730419B_ABST
    Figure CN118730419B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for sample container leakage testing, which comprises arranging a preset color-changing substance on the inner wall of the sample container, wherein the color-changing substance comprises anhydrous copper sulfate powder that changes color when in contact with water; immersing the sample container in water for a first preset time, or placing the sample container in a steam environment at a preset pressure for a second preset time; and determining whether the sample container leaks according to the color change of the color-changing substance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical devices, and in particular to a method for leak testing of a sample container. Background Art

[0002] The requirements for disposable containers used to collect human specimens are: they must be sturdy, there should be no leakage when they are properly covered with a lid or plug, and there should be no residue on the outside of the container.

[0003] At present, the standards or regulations adopted by China and foreign countries for the performance test of in vitro diagnostic medical devices - disposable containers for collecting human specimens are mainly: BS EN 14254-2004 and IS0 6717-2021. The leakage tests of these two standards use the same test method: using a sodium chloride aqueous solution containing a fixed ratio of fluorescein sodium and dextran, add the specimen container to the nominal capacity, and install the cover according to the manufacturer's regulations; then use a mixer to mix the specimen container filled with the solution, then invert the specimen container and immerse it in water for 60 minutes, take it out and place it under a long-wave ultraviolet (UV) light source for inspection.

[0004] This method is difficult to operate for many medical device companies that do not have in vitro diagnostic testing laboratories or solution mixing capabilities. It also requires additional solution reservoirs, long-wave ultraviolet (UV) light sources, mixers and other equipment. If the test is outsourced, the test cycle is long and the cost is high (usually 15 working days or longer, and the cost is >2K RMB). Moreover, many third-party laboratories do not have the qualifications to conduct this leak test.

[0005] Therefore, there is an urgent need for a leakage testing method that is simple to operate, fast and low-cost.

[0006] The above contents are only used to assist in understanding the technical solution of the present invention and do not constitute an admission that the above contents are prior art. Summary of the invention

[0007] The main purpose of the present invention is to provide a method for sample container leakage testing, aiming to solve the above-mentioned problems in the prior art.

[0008] To achieve the above object, the present invention provides a method for sample container leakage testing, comprising:

[0009] Arranging a preset color-changing substance on the inner wall of the sample container, wherein the color-changing substance includes anhydrous copper sulfate powder that changes color when in contact with water;

[0010] immersing the sample container in water for a first preset time, or placing the sample container in a steam environment at a preset pressure for a second preset time;

[0011] Whether leakage occurs in the sample container is determined according to the color change of the color-changing substance.

[0012] Preferably, in the method for testing leakage of a sample container, determining whether leakage occurs in the sample container according to the color change of the color-changing substance comprises:

[0013] When the color-changing substance is still white, it is determined that the sample container has not leaked;

[0014] When the color-changing substance at least partially changes from white to blue, it is determined that the sample container is leaking.

[0015] Preferably, in the method for testing leakage of a sample container, the step of arranging a preset color-changing substance on the inner wall of the sample container comprises:

[0016] Add anhydrous copper sulfate powder to the sample container;

[0017] Shaking the sample container to allow the anhydrous copper sulfate powder to fill all areas of the sample container;

[0018] Correspondingly, when the color-changing substance at least partially changes from white to blue, it is determined that the sample container leaks, including:

[0019] When at least a partial area of ​​the color-changing substance changes from white to blue, it is determined that leakage occurs in the color-changing area of ​​the sample container.

[0020] Preferably, in the method for sample container leakage testing, shaking the sample container to allow the anhydrous copper sulfate powder to fill various areas in the sample container comprises:

[0021] The sample container is placed in a shaking device and shaken to allow the anhydrous copper sulfate powder to fill all areas of the sample container.

[0022] Preferably, in the method for sample container leakage testing, the color-changing substance further includes an inert hygroscopic material, and the inert hygroscopic material is mixed with the anhydrous copper sulfate powder in a preset ratio.

[0023] Preferably, in the method for sample container leakage testing, the inert hygroscopic material comprises one or more of silica gel, molecular sieve, activated alumina, and anhydrous calcium sulfate.

[0024] Preferably, in the method for sample container leakage testing, the inert hygroscopic material is silica gel particles, the silica gel particles and the anhydrous copper sulfate powder are uniformly mixed in a preset ratio, and the mass ratio of the silica gel particles to the anhydrous copper sulfate powder is 1: (10-12).

[0025] Preferably, in the method for sample container leakage testing, the color-changing substance further comprises concentrated hydrochloric acid or concentrated sulfuric acid, and the ratio of the anhydrous copper sulfate powder to concentrated hydrochloric acid / concentrated sulfuric acid is (0.5-1): (2-5) (g / ml);

[0026] Correspondingly, the method of arranging a preset color-changing substance on the inner wall of the sample container includes:

[0027] Placing the anhydrous copper sulfate powder on the inner wall of the sample container;

[0028] The concentrated hydrochloric acid / concentrated sulfuric acid is added onto the anhydrous copper sulfate powder to fully contact the anhydrous copper sulfate powder with the concentrated hydrochloric acid / concentrated sulfuric acid.

[0029] Preferably, in the method for sample container leakage testing, the color-changing substance comprises the following raw materials in parts by mass:

[0030] The anhydrous copper sulfate powder: 1-3 parts;

[0031] Phenolphthalein for acid-base indication: 1-3 parts;

[0032] Macroporous adsorption resin: 1-3 parts;

[0033] Solvent: 15-20 parts.

[0034] Preferably, in the method for testing the leakage of a sample container, before the step of arranging a preset color-changing substance on the inner wall of the sample container, the method comprises:

[0035] First, the phenolphthalein and the anhydrous copper sulfate powder are uniformly mixed to obtain a first mixture;

[0036] Then, the first mixture is mixed with a macroporous adsorption resin and a solvent to form a color-changing solution;

[0037] Correspondingly, the method of arranging a preset color-changing substance on the inner wall of the sample container includes:

[0038] Brush the color-changing solution on the inner wall of the sample container, and perform a leakage test after it dries.

[0039] The present invention has at least the following beneficial effects:

[0040] The method for sample container leakage testing provided by the present invention comprises the following steps: firstly, a preset color-changing substance is arranged on the inner wall of the sample container, wherein the color-changing substance includes anhydrous copper sulfate powder that changes color when in contact with water; the sample container is immersed in water for a first preset time period, or the sample container is placed in a steam environment under a preset pressure for a second preset time period; and based on the color change of the color-changing substance, it is determined whether the sample container is leaking. Such a leakage testing method is simple to operate, fast and low-cost.

[0041] Furthermore, the test method does not require additional test equipment and has a fast test speed. Each self-test only requires a small amount of reagent (anhydrous copper sulfate powder, the reagent cost is about 2-3 RMB).

[0042] Furthermore, anhydrous copper sulfate powder is added to the sample container; the sample container is shaken to allow the anhydrous copper sulfate powder to fill various areas of the sample container. Assuming that there are gaps or cracks on the sample container, the sample container can be shaken to allow the color-changing substance to fill the gaps or cracks of the sample container during shaking, thereby more accurately testing whether leakage occurs with higher sensitivity.

[0043] Furthermore, the color-changing substance can also be a raw material including the following parts by mass: anhydrous copper sulfate powder: 1-3 parts; phenolphthalein for acid-base indication: 1-3 parts; macroporous adsorption resin: 1-3 parts; solvent: 15-20 parts. When in use, the color-changing solution can be brushed on the inner wall of the sample container; after drying, the sealing test can be carried out. In this way, the color-changing substance can be evenly distributed in every corner of the sample container, and the detection is more precise and accurate; the color-changing substance will not diffuse when it encounters water, and the specific location where the leakage occurs can be accurately determined. More specifically, when in use, first apply the color-changing solution to each area of ​​the sample container, seal it after the color-changing solution dries, and immerse it in an aqueous solution to observe the changes.

[0044] Furthermore, after the charged phenolphthalein is mixed with the anhydrous copper sulfate powder, the charged phenolphthalein first chelates with the copper sulfate to form a charged macromolecule; after being mixed with the macroporous adsorption resin, the charged macromolecule is adsorbed by the macroporous adsorption resin, and the adsorption force at this time is the intermolecular force and the coordination bond force. Since this adsorption force is very strong and will not be separated by the interference of external moisture, even if it is not completely dried during use, it will not cause the phenolphthalein to develop color and cause failure. When external moisture enters the color-changing substance, the macroporous adsorption resin fixes the phenolphthalein and absorbs moisture, so that it can develop color when it encounters water and will not diffuse; at the same time, the anhydrous copper sulfate powder will also develop color when it encounters water, which can further improve the color development effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1A schematic diagram of an embodiment of a method for leak testing of a sample container provided by the present invention.

[0046] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION

[0047] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with the embodiments. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0048] In the embodiments of the present invention, the term "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0049] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence.

[0050] In the embodiments of the present invention, the term "plurality" refers to two or more than two, and other quantifiers are similar.

[0051] In the present invention, unless otherwise specified, the directional words used, such as "up, down, top, bottom", usually refer to the directions shown in the drawings, or to the components themselves in the vertical, perpendicular or gravity directions; similarly, for ease of understanding and description, "inside and outside" refer to the inside and outside relative to the outline of each component itself, but the above-mentioned directional words are not used to limit the present invention.

[0052] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings. However, it can be understood by those skilled in the art that in the embodiments of the present invention, many technical details are proposed in order to enable the reader to better understand the present invention. However, even without these technical details and various changes and modifications based on the following embodiments, the technical scheme claimed in the present invention can also be implemented. The division of the following embodiments is for the convenience of description and should not constitute any limitation on the specific implementation of the present invention. The various embodiments can be combined and referenced with each other under the premise of no contradiction.

[0053] The present invention provides a method for leak testing of a sample container. Figure 1The schematic diagram of the method for sample container leakage testing provided by the present invention is shown. The method for sample container leakage testing is mainly used in containers for temporary or permanent storage of human samples in the medical field that need to be tested for sealing, such as disposable containers that can be used to collect human specimens (except blood).

[0054] In step S100, a preset color-changing substance is arranged on the inner wall of the sample container, wherein the color-changing substance includes anhydrous copper sulfate powder that changes color when in contact with water.

[0055] Copper sulfate (CuSO4) is an inorganic compound widely used in industrial production and scientific research. Copper sulfate (CuSO4) is a white or off-white powder, easily soluble in water, and turns into blue crystals or powder after hydration.

[0056] Anhydrous copper sulfate powder is placed in the sample container, and then the sample container is sealed according to the corresponding requirements. For example, for a disposable container for collecting human specimens, after the disposable container is opened, anhydrous copper sulfate powder is placed in the disposable container, and then the cover is installed according to the manufacturer's regulations of the disposable container.

[0057] It should be noted that the color-changing substance can be directly arranged at the bottom of the sample container, so that when the color-changing substance changes color after water enters the sample container, it can be determined that the sample container is not sealed well and leakage occurs; the color-changing substance can also be arranged in various areas of the sample container, so that when the color-changing substance in a certain area changes color, it can be determined which specific area has leakage.

[0058] When distributing the color-changing substance in various areas of the sample container, anhydrous copper sulfate powder may be added to the sample container; and then the sample container is shaken to allow the anhydrous copper sulfate powder to fill various areas of the sample container.

[0059] In addition, assuming that there are gaps or cracks on the sample container, by shaking the sample container, the color-changing substance can be filled into the gaps or cracks of the sample container during shaking, so that it is possible to more accurately test whether a leak occurs with higher sensitivity. When a gap or crack leaks, the color-changing substance contained in the gap or crack will change color. In addition, the gap or crack can be identified by shaking the sample container and filling the gap or crack with the color-changing substance. For different sample containers, assuming that gaps or cracks appear at the same position, it means that there is a problem with the manufacturing process of the sample container, and the manufacturing process of the sample container can be improved to improve the problem.

[0060] Furthermore, the anhydrous copper sulfate filled in the gap after shaking changes color, which has a higher sensitivity and is easier to observe after color change. On the contrary, if it is not shaken, the anhydrous copper sulfate powder in the sample container will accumulate together. If the sealing of the container is only slightly poor and little water enters, the accumulated anhydrous copper sulfate will be difficult to observe after color change.

[0061] In order to precisely control the force, time and angle of shaking the container and ensure consistency of each test condition, in some feasible implementations, the sample container with the color-changing substance is placed in a shaking device and shaken to fill the anhydrous copper sulfate powder in each area of ​​the sample container. This ensures that the degree of filling the gaps remains basically the same, and the test results are reliable.

[0062] Specifically, the operator wears a protective mask, goggles, and protective gloves as required, takes an unused, uncontaminated specimen container, opens the lid on the container, adds a nominal volume of copper sulfate (CuSO4) to the specimen container, and installs the cap in accordance with the manufacturer's regulations.

[0063] It is worth noting that the color-changing substance may only include anhydrous copper sulfate powder that changes color when in contact with water; it may also include other substances that can enhance the detection effect of anhydrous copper sulfate powder. For example, some inert hygroscopic materials (such as trace amounts of silica gel) may be added to the anhydrous copper sulfate powder for mixing. The inert hygroscopic material itself does not undergo a chemical reaction, but can quickly absorb moisture and form a local moisture environment on the surface, causing the anhydrous copper sulfate to change color faster. The inert hygroscopic material is a material that can absorb moisture but does not react chemically with the anhydrous copper sulfate. Specifically, the inert hygroscopic material is mixed with the anhydrous copper sulfate powder in a preset ratio.

[0064] The inert hygroscopic material includes one or more of silica gel, molecular sieve, activated alumina, and anhydrous calcium sulfate.

[0065] Silica Gel: Silica gel is a highly efficient desiccant, commonly used as a desiccant in industry and homes. Silica gel itself is an amorphous form of silicon dioxide (SiO2) with a highly porous structure that can quickly absorb moisture from the air. Silica gel is available in a variety of forms, including blue, orange, and transparent. The blue indicator silica gel will turn pink after absorbing moisture, which can help determine changes in humidity.

[0066] Molecular Sieves: Molecular sieves are artificial porous materials, usually composed of aluminosilicates. The pore size can be precisely controlled, so they can selectively adsorb water molecules and are widely used in gas separation and drying.

[0067] Activated Alumina: Activated alumina is a porous, high surface area adsorbent commonly used for drying liquids and gases. It has a strong hygroscopic capacity and is chemically inert and does not react with anhydrous copper sulfate.

[0068] Anhydrous Calcium Sulfate: Anhydrous Calcium Sulfate can also be used as a hygroscopic agent. It can absorb a certain amount of water and then convert into calcium sulfate dihydrate. This material is relatively mild and will not interfere with the hydration reaction of copper sulfate.

[0069] In this embodiment, silica gel particles are mixed with anhydrous copper sulfate powder. Since the hygroscopic properties of silica gel are derived from its porous structure, these holes can accommodate water molecules, and the moisture absorption speed is fast and the adsorption capacity is large. When used specifically, the composition and pore size of silica gel can be adjusted as needed to achieve the best moisture absorption effect.

[0070] The silica gel particles and the anhydrous copper sulfate powder are uniformly mixed according to a preset ratio. When the proportion of the silica gel particles is too large, the anhydrous copper sulfate will not absorb any water after absorbing water, resulting in failure to indicate color change; too small a proportion will result in no obvious effect. Therefore, in this embodiment, the mass ratio of the silica gel particles to the anhydrous copper sulfate powder is 1: (10-12), so that the silica gel can provide an appropriate amount of moisture absorption assistance without excessively robbing water, so that the anhydrous copper sulfate can react sensitively when there is a slight change in moisture inside the container.

[0071] In some other feasible embodiments, the color-changing substance includes the following raw materials in parts by weight: anhydrous copper sulfate powder: 1-3 parts; phenolphthalein for acid-base indication: 1-3 parts; macroporous adsorption resin: 1-3 parts; solvent: 15-20 parts.

[0072] Macroporous adsorption resin is a type of polymer adsorption resin that does not contain exchange groups and has a macroporous structure. It has a good macroporous network structure and a large specific surface area. It can selectively physically adsorb organic matter in aqueous solutions. It is a new type of organic polymer adsorbent developed in the 1960s and has been widely used in environmental protection, food, medicine and other fields.

[0073] The method for producing the color-changing substance comprises the following steps:

[0074] (1) firstly, uniformly mixing charged phenolphthalein and anhydrous copper sulfate powder to obtain a first mixture;

[0075] (2) The first mixture is then mixed with a macroporous adsorption resin and a solvent to form a color-changing solution.

[0076] When in use, the color-changing solution can be brushed on the inner wall of the sample container; after it dries, the sealing test can be performed. In this way, the color-changing substance can be evenly distributed in every corner of the sample container, and the detection is more precise and accurate; the color-changing substance will not diffuse when it encounters water, and the specific location where the leakage occurs can be accurately determined. More specifically, when in use, the color-changing solution is first applied to each area of ​​the sample container, and the color-changing solution is sealed after it dries, and then immersed in the aqueous solution to observe the changes.

[0077] After the charged phenolphthalein is mixed with the anhydrous copper sulfate powder, the charged phenolphthalein first chelates with the copper sulfate to form a charged macromolecule; after mixing with the macroporous adsorption resin, the charged macromolecule is adsorbed by the macroporous adsorption resin, and the adsorption force at this time is the intermolecular force and the coordination bond force. Since this adsorption force is very strong and will not be separated by the interference of external moisture, even if it is not completely dried during use, it will not cause the phenolphthalein to develop color and become ineffective. When external moisture enters the color-changing substance, the macroporous adsorption resin fixes the phenolphthalein and absorbs the moisture, so that it can develop color when it encounters water and will not diffuse; at the same time, the anhydrous copper sulfate powder will also develop color when it encounters water, which can further improve the color development effect.

[0078] In step S200, the sample container is immersed in water for a first preset time. Specifically, the sample container filled with the color-changing substance is immersed in water at room temperature, and the water immerses the sample container for a first preset time (e.g., 60 minutes or longer).

[0079] After the sample container with the color-changing substance is immersed in water for the first preset period of time, assuming that there is a problem with poor sealing, water will inevitably enter the sample container. At this time, when the color-changing substance includes anhydrous copper sulfate, if copper sulfate (CuSO4) is still white, it means that the specimen container is well sealed and the leakage test is qualified; if copper sulfate (CuSO4) appears blue, it means that the specimen container is not well sealed, there is leakage, and the leakage test fails.

[0080] It is worth noting that in some other feasible implementations, the sample container provided with the color-changing substance can also be placed in a steam environment and pressurized to promote test efficiency. When steam enters the sample container, if the color-changing substance includes anhydrous copper sulfate, if copper sulfate (CuSO4) is still white, it means that the sample container is well sealed and the leakage test is qualified; if copper sulfate (CuSO4) appears blue, it means that the sample container is not well sealed and leaks, and the leakage test is unqualified. The magnitude of the pressurization can be determined according to the requirements of the sample container.

[0081] The hydration reaction of anhydrous copper sulfate and water is:

[0082] CuSO4+5H2O→CuSO4·5H2O;

[0083] In order to accelerate the color change reaction of anhydrous copper sulfate, concentrated sulfuric acid or concentrated hydrochloric acid can be used. Concentrated sulfuric acid or concentrated hydrochloric acid can be added to anhydrous copper sulfate. In this way, H + Ions can promote these reactions because H + Ions can affect the equilibrium of the reaction, pushing the reaction to the right. An acidic environment helps form a more stable hydrate between anhydrous copper sulfate and water.

[0084] Take concentrated hydrochloric acid as an example. Concentrated hydrochloric acid has strong water absorption and can absorb water to form dilute hydrochloric acid. Therefore, if a small amount of water enters the sample container, the concentrated hydrochloric acid will absorb the water first. When the concentrated hydrochloric acid absorbs water, part of the concentrated hydrochloric acid will become dilute hydrochloric acid. + Ions can promote the hydration reaction of anhydrous copper sulfate, making it easier for anhydrous copper sulfate to absorb surrounding water. + ions, these H + Ions can enhance the attraction of anhydrous copper sulfate to water, causing the hydration reaction to occur faster and more thoroughly, thereby accelerating the change of anhydrous copper sulfate from white (or off-white) to blue copper sulfate pentahydrate.

[0085] When the anhydrous copper sulfate powder is mixed with concentrated hydrochloric acid / concentrated sulfuric acid, only concentrated sulfuric acid may be added to the anhydrous copper sulfate powder, only concentrated hydrochloric acid may be added, or concentrated hydrochloric acid and concentrated sulfuric acid may be added, and no specific restrictions are made here. When adding concentrated hydrochloric acid / concentrated sulfuric acid, if too little anhydrous copper sulfate is added, the color change cannot be obviously observed; too much anhydrous copper sulfate addition may cause the concentrated hydrochloric acid / concentrated sulfuric acid to fail prematurely or react too slowly; too little concentrated hydrochloric acid / concentrated sulfuric acid addition may not achieve the desired effect; too much concentrated hydrochloric acid / concentrated sulfuric acid addition may affect the observation effect of the color change of anhydrous copper sulfate. In this embodiment, the ratio of anhydrous copper sulfate powder to concentrated hydrochloric acid / concentrated sulfuric acid is (0.5-1): (2-5) (g / ml). At this time, the color change can be clearly observed, and the concentrated hydrochloric acid / concentrated sulfuric acid will not become ineffective prematurely or react too slowly due to an excessive amount of anhydrous copper sulfate powder. At this time, the amount of concentrated hydrochloric acid / concentrated sulfuric acid is sufficient to provide a strong acidic environment in the sealed container. At the same time, the volatility and water absorption of concentrated hydrochloric acid / concentrated sulfuric acid can quickly absorb the trace moisture entering the container, thereby promoting the color change of anhydrous copper sulfate.

[0086] Specifically, the concentrated hydrochloric acid / concentrated sulfuric acid is added onto the anhydrous copper sulfate powder disposed on the inner wall of the sample container, so that the anhydrous copper sulfate powder and the concentrated hydrochloric acid / concentrated sulfuric acid are fully in contact with each other.

[0087] During the operation, you can use a small spoon or other tool to put a certain amount of anhydrous copper sulfate powder into the bottom of a sealed container; then, carefully add a small amount of concentrated hydrochloric acid on the anhydrous copper sulfate powder to ensure that they are in contact with each other; then immediately seal the container to ensure that the container is well sealed.

[0088] In step S300, whether leakage occurs in the sample container is determined according to the color change of the color-changing substance.

[0089] Specifically, when the color-changing substance is still white, it is determined that the sample container has not leaked; when the color-changing substance at least partially changes from white to blue, it is determined that the sample container has leaked.

[0090] When deteriorated substances are distributed in all areas of the sample container, and at least a portion of the color-changing substances changes from white to blue, it is determined that leakage occurs in the color-changing area of ​​the sample container.

[0091] Obviously, the embodiments described above are only some embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, ordinary technicians in this field can make other different forms of changes or modifications without creative work, which should fall within the scope of protection of the present invention.

Claims

1. A method for leak testing of a sample container, characterized in that: include: Arranging a preset color-changing substance on the inner wall of a sample container, shaking the sample container, so that the color-changing substance fills various areas of the sample container, the color-changing substance comprising anhydrous copper sulfate powder that changes color when in contact with water; immersing the sample container in water for a first preset time, or placing the sample container in a steam environment at a preset pressure for a second preset time; Determining whether the sample container leaks according to the color change of the color-changing substance; The color-changing substance comprises the following raw materials in parts by mass: 1-3 parts of anhydrous copper sulfate powder; Phenolphthalein for acid-base indication: 1-3 parts; Macroporous adsorption resin: 1-3 parts; Solvent: 15-20 parts; The color-changing substance further includes an inert hygroscopic material, and the inert hygroscopic material is mixed with the anhydrous copper sulfate powder according to a preset ratio; The color-changing substance also includes concentrated hydrochloric acid or concentrated sulfuric acid, and the ratio of the anhydrous copper sulfate powder to the concentrated hydrochloric acid / concentrated sulfuric acid is (0.5-1): (2-5) (g / ml); Correspondingly, the method of arranging a preset color-changing substance on the inner wall of the sample container includes: Placing the anhydrous copper sulfate powder on the inner wall of the sample container; The concentrated hydrochloric acid / concentrated sulfuric acid is added onto the anhydrous copper sulfate powder to fully contact the anhydrous copper sulfate powder with the concentrated hydrochloric acid / concentrated sulfuric acid.

2. The method for sample container leakage testing according to claim 1, characterized in that: The step of determining whether the sample container leaks according to the color change of the color-changing substance comprises: When the color-changing substance is still white, it is determined that the sample container has not leaked; When the color-changing substance at least partially changes from white to blue, it is determined that the sample container is leaking.

3. The method for sample container leakage testing according to claim 2, characterized in that: The method of arranging a preset color-changing substance on the inner wall of the sample container, wherein the color-changing substance fills each area of ​​the sample container, comprises: Add anhydrous copper sulfate powder to the sample container; Shaking the sample container to allow the anhydrous copper sulfate powder to fill all areas of the sample container; Correspondingly, when the color-changing substance at least partially changes from white to blue, it is determined that the sample container leaks, including: When at least a partial area of ​​the color-changing substance changes from white to blue, it is determined that leakage occurs in the color-changing area of ​​the sample container.

4. The method for sample container leakage testing according to claim 3, characterized in that: The step of shaking the sample container so that the anhydrous copper sulfate powder fills all areas of the sample container includes: The sample container is placed in a shaking device and shaken to allow the anhydrous copper sulfate powder to fill all areas of the sample container.

5. The method for sample container leakage testing according to claim 1, characterized in that: The inert hygroscopic material includes one or more of silica gel, molecular sieve, activated alumina, and anhydrous calcium sulfate.

6. The method for sample container leakage testing according to claim 1, characterized in that: The inert hygroscopic material is silica gel particles, and the silica gel particles are evenly mixed with the anhydrous copper sulfate powder according to a preset ratio, and the mass ratio of the silica gel particles to the anhydrous copper sulfate powder is 1: (10-12).

7. The method for sample container leakage testing according to claim 1, characterized in that: Before the step of arranging a preset color-changing substance on the inner wall of the sample container, the method includes: First, the phenolphthalein and the anhydrous copper sulfate powder are uniformly mixed to obtain a first mixture; Then, the first mixture is mixed with a macroporous adsorption resin and a solvent to form a color-changing solution; Correspondingly, the method of arranging a preset color-changing substance on the inner wall of the sample container includes: Brush the color-changing solution on the inner wall of the sample container, and perform a leakage test after it dries.

Citation Information

Patent Citations

  • Printing ink capable of discoloring when encountering water and being indiffusible as well as preparation method and application of printing ink

    CN108504167A

  • Airtightness detection device for sealed cabin for biopharmacy

    CN216081928U